Effectiveness of Oxytocin Massage on Increasing Breast Milk Production in Breastfeeding Mothers and Infant Weight Gain - Risa Pitriani; Megasari, Miratu (Yayasan Ahmad Mansyur Nasirah, 2024)
Oxytocin massage is a massage of the 5-6th rib of the spine down to the scapula which will speed up the work of the sympathetic nerves in stimulating the posterior pituitary to release oxytocin. Based on the health profile of Riau Province, the coverage of babies given exclusive breastfeeding up to 6 months of age in Riau Province in 2020 decreased by (47%) and from the survey results at the Arrabih Pratama Clinic, there were several mothers who did not know about oxytocin massage to increase breast milk production. The aim of the research is to determine the effectiveness of oxytocin massage in increasing breast milk production and increasing baby weight at the Arrabih Pratama Clinic. This research method has a type of quantitative analytical research with a Quasi-Experimental design using a two-group posttest to test paired variables. This research was conducted at the Arrabih Pratama Clinic on 21 August – 21 September 2023. The population in this study were all postpartum mothers who visited the Arrabih Pratama Clinic and the samples in this study were 30 postpartum mothers who were breastfeeding who were divided into 2 intervention groups and controls. The sampling technique in this research used Total Sampling based on certain considerations according to inclusion and exclusion criteria. The results of this study showed that there was an effect of oxytocin massage on increasing breast milk production in breastfeeding mothers and increasing baby weight. Based on research results, giving oxytocin massage to breastfeeding mothers can increase breast milk production and increase baby weight gain. Suggestions for the clinic to provide oxytocin massage facilities and attend mother and baby massage training.